Asset Concealment through Corporate Structures in Money Laundering Offenses and the Constitutional Challenges of Natural Resource Governance in Indonesia - Mardiah Mastur Rahmah; Kintan Artari; Rachmat Ragil Iskandar; Muhammad Nurcholis Alhadi (Constitutional Law Review, 2026)
This study examines the use of corporate entities to conceal illicit assets in money laundering schemes in Indonesia as a constitutional economic governance issue rather than merely an economic crime problem. Employing normative legal research through statutory, conceptual, and case approaches, it explores the relationship between anti-money laundering regulation, beneficial ownership transparency, corporate criminal liability, asset recovery, and the constitutional mandate embodied in Article 33 of the 1945 Constitution. The findings demonstrate that corporate structures can obscure the nexus between offenders, illicit assets, and predicate offences through complex ownership arrangements and effective control mechanisms. In the natural resources sector, such practices undermine the State’s capacity to safeguard public wealth and restore economic benefits to society. The study argues that beneficial ownership transparency, corporate liability, and asset recovery should be reconceptualized as constitutional instruments for strengthening accountability, economic governance, and the recovery of assets for the public interest.